Grade 1 Endometrioid Endometrial Carcinoma Presenting with Pelvic Bone Metastasis: A Case Report and Review of the Literature - My-Linh T. Nguyen; Christopher J. LaFargue; Tarah L. Pua; Sean S. Tedjarati (Case Reports in Obstetrics and Gynecology)
Most grade 1 endometrioid endometrial cancers are confined to the uterus at the time of diagnosis and confer a good prognosis. Rarely will a grade 1 endometrioid endometrial carcinoma present with distant metastasis, especially to the bone. We present the case of a 56-year-old woman with postmenopausal bleeding and right hip pain due to metastatic grade 1 endometrioid uterine cancer invading into the right ischium. We discuss treatment options as well as provide a review of prior published reports on bony metastasis in grade 1 endometrioid endometrial cancers. To date, this case is one of 10 others which demonstrates that even a well-differentiated, low-grade endometrioid endometrial carcinoma can progress in a highly aggressive manner.